Global Epidemiology of Tuberculosis - Glaziou, Philippe; Floyd, Katherine; Raviglione, Mario C. (Seminars in Respiratory and Critical Care Medicine, 2018)
Tuberculosis (TB) was the underlying cause of 1.3 million deaths among human immunodeficiency virus (HIV)-negative people in 2016, exceeding the global number of HIV/acquired immune deficiency syndrome (AIDS) deaths. In addition, TB was a contributing cause of 374,000 HIV deaths. Despite the success of chemotherapy over the past seven decades, TB is the top infectious killer globally. In 2016, 10.4 million new cases arose, a number that has remained stable since the beginning of the 21th century, frustrating public health experts tasked to design and implement interventions to reduce the burden of TB disease worldwide. Ambitious targets for reductions in the epidemiological burden of TB have been set within the context of the Sustainable Development Goals (SDGs) and the End TB Strategy. Achieving these targets is the focus of national and international efforts, and demonstrating whether or not they are achieved is of major importance to guide future and sustainable investments. This article reviews epidemiological facts about TB, trends in the magnitude of the burden of TB and factors contributing to it, and the effectiveness of the public health response.
Keywords: tuberculosis; epidemiology; disease burden; incidence; mortality; risk factors; latent infection